RIPK1 mutations causing infantile-onset IBD with inflammatory and fistulizing features - Sultan, Mutaz; Adawi, Mohammad; Kol, Nitzan; McCourt, Blake; Adawi, Ihda; Baram, Liran; Tal, Noa; Werner, Lael; Lev, Atar; Snapper, Scott B.; Barel, Ortal; Konnikova, Liza; et al. (Frontiers in Immunology, 2022)
Purpose Receptor-interacting serine/threonine-protein kinase 1 (RIPK1) is an important regulator of necroptosis and inflammatory responses. We present the clinical features, genetic analysis and immune work-up of two patients with infantile-onset inflammatory bowel disease (IBD) resulting from RIPK1 mutations. Methods Whole exome and Sanger sequencing was performed in two IBD patients. Mass cytometry time of flight (CyTOF) was conducted for in-depth immunophenotyping on one of the patient’s peripheral blood mononuclear cells, and compared to control subjects and patients with Crohn’s disease. Results The patients presented with severe colitis and perianal fistulas in the first months of life, without severe/atypical infections. Genetic studies identified pathogenic genetic variants in RIPK1 (Patient 1, A c.1934C>T missense mutation in Exon 11; Patient 2, c.580G>A missense mutation residing in Exon 4). Protein modeling demonstrated that the mutation in Patient 1 displaces a water molecule, potentially disrupting the local environment, and the mutation in Patient 2 may lead to disruption of the packing and conformation of the kinase domain. Immunofluorescence RIPK1 staining in rectal biopsies demonstrated no expression for Patient 1 and minimal expression for Patient 2, compared to controls and patients with active Crohn’s disease. Using CyTOF unbiased clustering analysis, we identified peripheral immune dysregulation in one of these patients, characterized by an increase in IFNγ CD8+ T cells along with a decrease in monocytes, dendritic cells and B cells. Moreover, RIPK1-deficient patient’s immune cells exhibited decreased IL-6 production in response to lipopolysaccharide (LPS) across multiple cell types including T cells, B cells and innate immune cells. Conclusions Mutations in RIPK1 should be considered in very young patients presenting with colitis and perianal fistulas. Given RIPK1’s role in inflammasome activation, but also in epithelial cells, it is unclear whether IL1 blockade or allogeneic hematopoietic stem cell transplantation can suppress or cure the hyper-inflammatory response in these patients. Additional studies in humans are required to better define the role of RIPK1 in regulating intestinal immune responses, and how treatment can be optimized for patients with RIPK1 deficiency.